2022
DOI: 10.1093/ofid/ofac271
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Streptomyces spp. in a Clinical Sample: Always Contamination? Results of a French Retrospective Study

Abstract: Background Streptomyces are environmental Gram-positive bacilli that can cause ubiquitous mycetoma and, more rarely, invasive infections. We describe the clinical relevance of Streptomyces spp. identified in human samples and characteristics of patients with invasive Streptomyces infections. Methods We conducted a retrospective (2006-2017) study of Streptomyces isolates identified in clinical samples in French microbiology la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…They found that Streptomyces species were most susceptible to amikacin, gentamycin, vancomycin, and linezolid, and exhibited high susceptibility to tetracycline and clarithromycin, while showing intrinsic resistance to penicillin ( Kotrbová et al., 2022 ). Similarly, in two retrospective studies of human clinical samples, amikacin and linezolid covered 100% of the Streptomyces isolates ( Sáez-Nieto et al., 2021 ; Gras et al., 2022 ). Consistent with these studies, our AST results showed that the pathogen was sensitive to clarithromycin, amikacin, and linezolid.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…They found that Streptomyces species were most susceptible to amikacin, gentamycin, vancomycin, and linezolid, and exhibited high susceptibility to tetracycline and clarithromycin, while showing intrinsic resistance to penicillin ( Kotrbová et al., 2022 ). Similarly, in two retrospective studies of human clinical samples, amikacin and linezolid covered 100% of the Streptomyces isolates ( Sáez-Nieto et al., 2021 ; Gras et al., 2022 ). Consistent with these studies, our AST results showed that the pathogen was sensitive to clarithromycin, amikacin, and linezolid.…”
Section: Discussionmentioning
confidence: 93%
“…Known for their ability to produce rich and diverse secondary metabolites, they have been widely used in clinical medicine ( Del Carratore et al., 2022 ). Despite the tremendous contributions of Streptomyces to medicine, they also pose risks as potential pathogens in humans, and particularly in immunocompromised patients ( Herbrík et al., 2020 ; Gras et al., 2022 ). Among the documented cases of Streptomyces infection, only a few have been described as clinical isolates relevant to humans ( McNeil et al., 1990 ; Gras et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations